Estimating Unit Cost for Dental Services: Evidence from Community Health Centers in Iran - Vatandoost, Vahid; Ebrahimipour, Hossein; Yousefi, Mahdi; Farahmand, Kazem; Esmaeilie, Reza (Journal of Dental School, 2020)
Objectives: Cost information can help policy makers to set user fees, public and private tariffs and budgets and also to conduct an economic evaluation to provide health care with acceptable quality and affordable price. This study aimed to do a cost analysis for the Iranian Comprehensive Health Centers (CHCs), to estimate the unit cost of different dental services. Methods: This was a cross-sectional study. Capital and recurrent cost information of three urban CHCs in Mashhad was collected. Cost identification was based on the provider’s perspective. The step-down costing method was adopted from Konte and Waker and applied in five steps: defining cost centers, identification of operational activities, assigning inputs to cost centers, allocate all costs to final centers, and compute unit costs. Results: In dental services, the most important cost driver was human resources that comprised 69% of the total cost. The unit cost of a relative K for dental care was 12,189 Rials (1 USD: 31,407 Rials as in 2016). Accordingly, the unit cost for different dental services varied from 182,834 Rials for dental radiography to 1,589,570 Rials for class II composite restoration. The mean cost of a dental visit for examination and diagnosis estimated 247,436 Rials. Conclusion: Comparison between the estimated unit cost and the current dental tariffs reveled considerable differences. Integration of dental services to primary health care in the Iranian CHCs would result in the economies of scope.